# What is the equation of the line normal to # f(x)=-sqrt((x+1)(x+3)# at # x=0#?

Now we will compute the slope of the normal line:

therefore our line is given by

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the line normal to f(x) = -sqrt((x+1)(x+3)) at x=0 is y = -1.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the slope of a line tangent to the curve #3y^2-2x^2=1#?
- How do you use the definition of a derivative to find the derivative of #G(t)= (4t)/(t+1)#?
- How do you find the derivative of #y = sqrt(x + 1)# using the limit definition?
- How do you use the limit definition of the derivative to find the derivative of #f(x)=-4#?
- What is the equation of the line normal to #f(x)=x^2-3x # at #x=2#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7